Gender-Related Reading, Writing, and Charlotte Bronte: : Does a Woman Reader Make a Difference? - Bajner, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
In the past two decades feminist critics have demonstrated that gender leaves its traces in literary texts. They argue that gender determines everything, including value systems and language structures; as Elizabeth Abel said, “sexuality and textuality both depend on difference” (173). The introduction of gender—which is biological sex in the world of culture—into the field of literary studies works as a new phase in feminist criticism, claiming that all reading and writing, by men as well as by women, is marked by gender. By the time gender studies enter literary studies as critical discourse it is one more way of talking about books, authors and readers. This paper attempts to reveal how reading and writing relate to gender while focusing on female writers in general, and on Charlotte Bronte and her female audience in particular.